The “Messianic” Anointing of Jesus (Mark 14:3—9) - Guijarro Oporto, Santiago (Biblical theology bulletin, 2011)
Two peculiar elements of the Markan account of the anointing of Jesus in Bethany—the anointing of the head and the mandate to remember—suggest that the evangelist has transformed this memory into a rite by which Jesus is anointed as Messiah. This new ritual redefines the traditional rite of royal anointing to give new significance to the messianic character of Jesus. The mandate to remember the woman’s gesture and the critical moment in which Mark has placed the scene reveal that this new understanding of what it means to be the Messiah is key to the true identity of Jesus and of his followers.